Mitochondrial inorganic polyphosphate is required to maintain proteostasis within the organelle - Da Costa, Renata T.; Urquiza, Pedro; Perez, Matheus M.; Du, YunGuang; Khong, Mei Li; Zheng, Haiyan; Guitart-Mampel, Mariona; Elustondo, Pia A.; Scoma, Ernest R.; Hambardikar, Vedangi; Ueberheide, Beatrix; Tanner, Julian A.; et al. (Frontiers in Cell and Developmental Biology, 2024)
The existing literature points towards the presence of robust mitochondrial mechanisms aimed at mitigating protein dyshomeostasis within the organelle. However, the precise molecular composition underlying these mechanisms remains unclear. Our data show that inorganic polyphosphate (polyP), a polymer well-conserved throughout evolution, is a component of these mechanisms. In mammals, mitochondria exhibit a significant abundance of polyP, and both our research and that of others have already highlighted its potent regulatory effect on bioenergetics. Given the intimate connection between energy metabolism and protein homeostasis, the involvement of polyP in proteostasis has also been demonstrated in several organisms. For example, polyP is a bacterial primordial chaperone, and its role in amyloidogenesis has already been established.Here, using HEK293 cells, our study reveals that the depletion of mitochondrial polyP leads to increased protein aggregation within the organelle, following stress exposure. Furthermore, mitochondrial polyP is able to bind to proteins, and these proteins differ under control and stress conditions. The depletion of mitochondrial polyP significantly affects the proteome under both control and stress conditions, while also exerting regulatory control over gene expression. Our findings suggest that mitochondrial polyP is a previously unrecognized, and potent component of mitochondrial proteostasis.